Densidade populacional de felídeos e riqueza de mamíferos terrestres no sul da Amazônia - Trinca, Cristiano Trapé (2014)
The objective of the present study was to estimate the population density of jaguar (Panthera onca) and ocelot (Leopardus pardalis), and the abundance and species richness of other terrestrial mammals on the Fazenda São Nicolau, in the north of the Brazilian state of Mato Grosso, located in the southern Amazon basin. Camera traps were used to record the presence of the different species. Twelve collecting points were established in forested areas and sampled during four years between 2008 and 2011, with a total of 3603 trap-days of records. In impacted areas, 16 points were sampled in a rotating system over two years (2009 and 2010), with a total of 658 traps-days of records. Population parameters were estimated for the felids only in the forested areas, while the mammal community was analyzed in both habitats. Population density was estimated considering both open and closed populations, with individuals being identified based on pelage coloration patterns. The conventional capture-recapture method (CAPTURE) and the Spatially Explicit (SECR) model were used for the closed population analysis, while the Jolly-Seber and Pollock's robust design were used for the open population. A total of 10 jaguar were identified from 88 photo-records. Jaguar sexual ratio was estimate in 1,5:1. Population estimates of the jaguar were performed only for 2010 using closed population models. Population density based on the CAPTURE and the maximum distance traveled (MMDM) average was estimated at 4.12 ind/km ². The SECR estimated density was 3.03 (±1,57) ind/km ². Overall, 24 ocelots were identified from 134 photo-records, with density being estimated for all four years based on both open and closed population models. Ocelot sexual ratio was 1:1. Population density was estimated in the four seasons following the use of closed and open population analysis. The results of the SECR were more moderate, estimating 7.87 (± 3.0), 14.17 (± 6.5), 10.46 (± 4.4) and 7.36 (± 2.9) ind/km² between 2008 and 2011, respectively. The Jolly-Seber model obtained the highest estimates, 19.54, 25.01, 16.03 and 19.74 ind. / km ², each season. Survival and population growth were also estimated for this species. This result indicates that the spatially explicit model was adequate for the understanding of the population dynamics of the two felid species, although the robust design returned a greater number of demographic parameters, complementing the population analysis. The average population density of the ocelot for four seasons in southern Amazonia based on SECR, was estimated on 11.81 (± 2.29) ind/100km2 in a region with at least 25% of the disturbed area. Total mammalian richness for the study area was estimated at 26 species, with between 21 and 24 species being recorded in any given year. In the altered habitat, species richness was estimated to be 18 species, although only 17 were recorded (13 in one year and 15 in the other). The most common species were Tayassu pecari in the forested area and Cerdocyon thous in the altered habitat. The analysis of 24 indices of Beta diversity indicated a more homogeneous distribution of species in the forested areas in comparison with the altered habitat. Overall, this study has demonstrated that camera-trapping studies of population density or community structure require monitoring over two or more years for the collection of data for reliable analyses. This reinforces the importance of long-term studies for the understanding of the dynamics of wild populations and community structure.